1999
DOI: 10.1002/(sici)1520-6769(199911/12)25:3<121::aid-nrc1>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microdialysis evidence that midazolam facilitates propofol-induced reduction in rat accumbal dopamine release

Abstract: The aim of this study was to determine whether propofol reduces extracellular concentrations of dopamine in the rat nucleus accumbens and, if so, whether this effect is potentiated by midazolam. Propofol and midazolam were administered intravenously, via the external jugular vein, to freely‐moving rats. The extracellular concentrations of dopamine in the nucleus accumbens were measured consecutively every 25 min by using in vivo brain microdialysis with electrochemical detection. Propofol (2.5, 5.0 and 10.0 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It is possible that the electrophysiological results represent a disinhibition of DA neural activity in the VTA (O'Brien and White, 1987;Tan et al, 2010), which increases both the frequency and amplitude of accumbal transient release events. By contrast, the microdialysis results (Zetterström and Fillenz, 1990;Invernizzi et al, 1991;Finlay et al, 1992Finlay et al, , 1995Takada et al, 1993;Murai et al, 1994;Dazzi et al, 1995;Hegarty and Vogel, 1995;Motzo et al, 1997;Yoshida et al, 1999;Bentue-Ferrer et al, 2001;Rada and Hoebel, 2005;Gomez-A et al, 2017) and the recent anesthetized FSCV study (Gomez-A et al, 2017) might represent a localized suppression of accumbal DA release events. However, it should also be noted that the aforementioned electrophysiological studies identified dopamine neurons solely using electrophysiological criteria-which is now considered insufficient to determine whether a recorded unit is DAergic or GABAergic (Ungless et al, 2004;Ungless and Grace, 2012).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…It is possible that the electrophysiological results represent a disinhibition of DA neural activity in the VTA (O'Brien and White, 1987;Tan et al, 2010), which increases both the frequency and amplitude of accumbal transient release events. By contrast, the microdialysis results (Zetterström and Fillenz, 1990;Invernizzi et al, 1991;Finlay et al, 1992Finlay et al, , 1995Takada et al, 1993;Murai et al, 1994;Dazzi et al, 1995;Hegarty and Vogel, 1995;Motzo et al, 1997;Yoshida et al, 1999;Bentue-Ferrer et al, 2001;Rada and Hoebel, 2005;Gomez-A et al, 2017) and the recent anesthetized FSCV study (Gomez-A et al, 2017) might represent a localized suppression of accumbal DA release events. However, it should also be noted that the aforementioned electrophysiological studies identified dopamine neurons solely using electrophysiological criteria-which is now considered insufficient to determine whether a recorded unit is DAergic or GABAergic (Ungless et al, 2004;Ungless and Grace, 2012).…”
Section: Discussionmentioning
confidence: 93%
“…2011), it remains unclear how they alter DA release. All drugs of abuse are thought to increase brain DA levels (Di Chiara and Imperato, 1988), and the electrophysiology literature indicates that BZPs disinhibit VTA DA neurons (Tan et al, 2010(Tan et al, , 2011; however, the microdialysis literature generally reports that BZPs decrease accumbal DA concentration (Zetterström and Fillenz, 1990;Invernizzi et al, 1991;Finlay et al, 1992Finlay et al, , 1995Takada et al, 1993;Murai et al, 1994;Dazzi et al, 1995;Hegarty and Vogel, 1995;Motzo et al, 1997;Yoshida et al, 1999;Bentue-Ferrer et al, 2001;Rada and Hoebel, 2005; Gomez-A et al, 2017), but see Bentue-Ferrer et al (2001). Although microdialysis studies show a net reduction in extracellular DA concentration, the temporal resolution provided by this technique makes it difficult to discern whether a reduction in the amplitude of transient release events contributes to this effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the initial evidence that benzodiazepines decrease tonic dopamine date from the early 1990s, until recently it was generally accepted that all drugs of abuse, including benzodiazepines, cause an increase in the concentration of mesolimbic dopamine (Tan et al, 2010). However, this hypothesis was not supported by most microdialysis and PET studies, showing that benzodiazepines decrease dopamine concentrations in the dorsal and ventral striatum of several species (Dewey et al, 1992;Finlay et al, 1992;Gomez-A et al, 2017;Murai et al, 1994;Takada et al, 1993;Yoshida et al, 1999;Zetterström & Fillenz, 1990; but see Keller & Goeders, 2019). FSCV studies also showed that diazepam also diminished spontaneous and evoked phasic release of dopamine in the NAc and dorsal striatal of rodents (Brodnik et al, 2019;Gomez-A et al, 2017;Lopes et al, 2019;Schelp et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the VTA, benzodiazepines disinhibit DA neuron firing through action at local GABAergic interneurons [ 126 ], which in principle would result in increased DA levels in the NAc. However, at the level of the NAc, benzodiazepines are documented to reduce basal DA levels in studies employing in vivo microdialysis [ 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 ] and to attenuate evoked DA release in studies employing ex vivo and in vivo fast-scan cyclic voltammetry [ 37 , 47 , 136 ]. Direct recordings from DA axons in striatum have demonstrated that diazepam enhances the effects of striatal GABA tone at GABA A receptors on DA axons, further inhibiting DA release [ 47 ].…”
Section: Clinical Implications For Gabaergic Regulation Of Striatamentioning
confidence: 99%